PENGARUH KOMPOSISI MEDIA BUATAN UNTUK PERTUMBUHAN ULAT GRAYAK Spodoptera litura - Nurhajijah Nurhajijah; Wahyuni Umami Harahap; Ade Firmansyah Tanjung (LPPM Universitas Al Asyariah Mandar, 2022)
S. litura is a polyphagous pest that has many hosts. Here we use some leaves which are the host of S. litura. Provision of artificial feed in the laboratory as a substitute for natural feed for S. litura. The success of this research can be applied to plantations and farmers to develop parasitoids in the laboratory because parasitoid hosts are readily available in the laboratory. The results showed that the mortality of S. litura on artificial diet was 20% because the growth media of moldy S. litura showed black and gray color changes. Fungal contamination occurs during late instar larvae, larvae that die due to fungal contamination. Artificial feeding with different compositions showed different results. The average growth on soybean leaf artificial media showed the largest growth at the time of larvae (37.6 mm). Sequentially, the next largest larval growth was on corn artificial diet (33.87 mm) and the smallest was the growth of S. litura on palm leaf artificial media (33.56 mm). The average stage in the larval stage of each artificial diet treatment did not show any difference in larval age. Likewise in the adult phase the difference was only seen in the treatment of artificial diet soybean leaf feed (5.20 days). This value is the highest compared to the treatment on artificial diet of corn leaves and oil palm leaves with a value of (5.00 days). In the larval phase the number of instars was the same from each treatment and in the instar phase none experienced a long larval phase. This shows the composition of the artificial diet is very good.